Nonaqueous electrolyte electricity storage element
By using the positive electrode containing tungsten element and the negative electrode of solid graphite in the nonaqueous electrolyte storage element, the void ratio and porosity of graphite particles is controlled, and the problem of lowering input energy in high temperature environment is solved, and high energy density and stability are achieved .
Patent Information
- Application Number
- CN202380041382.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2023-05-17
- Publication Date
- 2025-01-14
AI Technical Summary
The existing non-aqueous electrolyte power storage components have difficulty maintaining the initial level of energy input under high temperature environments, and the dissolution of tungsten element leads to an increase in resistance, affecting the energy density.
Using a positive electrode active material containing tungsten elements and a negative electrode active material of solid graphite, the dissolution and resistance increase of tungsten elements are inhibited by controlling the void ratio and porosity of graphite particles.
Maintaining high input energy in initial and high temperature environments improves the energy density and stability of the nonaqueous electrolyte power storage element.
Smart Images

Figure CN119318050A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a non-aqueous electrolyte storage element. Background Art
[0002] Non-aqueous electrolyte secondary batteries represented by lithium-ion secondary batteries are mostly used in electronic devices such as personal computers, communication terminals, and automobiles due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte between the electrodes, and are configured to complete charging and discharging by receiving and receiving charge transfer ions between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium-ion capacitors and double-layer capacitors are also widely used.
[0003] The positive electrode active material for non-aqueous electrolyte storage element uses lithium transition metal composite oxides, polyanion compounds, etc. In order to improve the performance of non-aqueous electrolyte storage element, the surface of the particles of positive electrode active material is also coated with other compounds. In patent document 1, a positive electrode material for lithium secondary battery formed by coating the surface of particles of lithium manganese composite oxide with metal oxides such as titanium oxide and tin oxide is recorded. On the other hand, carbon materials headed by graphite are widely used for negative electrode active materials (refer to patent document 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-6676
[0007] Patent Document 2: Japanese Patent Application Publication No. 2005-222933 Summary of the invention
[0008] It is expected that the initial input energy of the non-aqueous electrolyte storage element is large and that the input energy is difficult to decrease even after storage in a high temperature environment. It should be noted that the input energy refers to the energy (power: W) that the non-aqueous electrolyte storage element can obtain per unit time during charging. In other words, the input energy refers to the input power during charging.
[0009] An object of the present invention is to provide a non-aqueous electrolyte storage element having a large input energy both initially and after storage in a high temperature environment.
[0010] A nonaqueous electrolyte storage device according to one aspect of the present invention includes a positive electrode including a positive electrode active material containing a tungsten element and a negative electrode including solid graphite.
[0011] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte electricity storage element having a large input energy both initially and after storage in a high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a perspective view showing one embodiment of a non-aqueous electrolyte electricity storage element.
[0013] Figure 2 This is a schematic diagram showing one embodiment of an electricity storage device constituted by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION
[0014] First, the outline of the nonaqueous electrolyte energy storage device disclosed in this specification will be described.
[0015] [1] A non-aqueous electrolyte storage device according to one aspect of the present invention comprises: a positive electrode including a positive electrode active material containing a tungsten element; and a negative electrode including solid graphite.
[0016] The input energy of the non-aqueous electrolyte storage element described in [1] above is large at the beginning and after storage in a high temperature environment. Although the reason is not clear, it is speculated to be the following. By using a positive electrode active material containing tungsten, the resistance of the positive electrode is reduced, and the initial input energy of the non-aqueous electrolyte storage element is increased. However, when the non-aqueous electrolyte storage element is stored in a high temperature environment, the tungsten element contained in the positive electrode active material is dissolved in the non-aqueous electrolyte. The dissolved tungsten element is precipitated on the negative electrode, which becomes the cause of the increase in the resistance of the negative electrode. As a result, the input energy of the non-aqueous electrolyte storage element is reduced. In particular, when the tungsten element is precipitated into the interior of the negative electrode active material particles, the resistance is further increased and the input energy is reduced. Therefore, it is believed that when solid graphite with less internal voids is used as the negative electrode active material, the tungsten element dissolved from the positive electrode active material can be suppressed from precipitating into the interior of the graphite particles, thereby suppressing the increase in the resistance of the negative electrode. Based on such reasons, it is speculated that the input energy of the non-aqueous electrolyte storage element described in [1] above is large at the beginning and after storage in a high temperature environment.
[0017] The "solid" of solid graphite means that the inside of the graphite particles is clogged and there are substantially no voids. More specifically, "solid" means that in the cross-section of the particles observed in the SEM image obtained using a scanning electron microscope (SEM), the area ratio (void ratio) of the voids in the particles relative to the total area of the particles is 2% or less.
[0018] The “area ratio of voids within the particle to the entire area of the particle (void ratio)” of the graphite particle can be determined by the following procedure.
[0019] (1) Preparation of test samples
[0020] The negative electrode to be measured is fixed with a thermosetting resin. For the negative electrode fixed by the resin, a cross-section polisher is used to expose the cross section and prepare a sample for measurement. It should be noted that the negative electrode to be measured is prepared by the following steps. When the negative electrode before assembling the non-aqueous electrolyte storage element can be prepared, it is used directly. When preparing from an assembled non-aqueous electrolyte storage element, the non-aqueous electrolyte storage element is first discharged at a constant current of 0.1C to the discharge end voltage during normal use as a discharged state. Disassemble the non-aqueous electrolyte storage element in this discharged state and take out the negative electrode. The taken out negative electrode is used as the working electrode, and a half-cell using metal Li as the counter electrode is assembled. When the open circuit voltage of the half-cell is less than 0.6V, the half-cell is discharged at a current of 0.1C in a manner that makes the open circuit voltage greater than 0.6V. It should be noted that the discharge of the above-mentioned half-cell refers to an oxidation reaction that releases charge transport ions from graphite as a negative electrode active material. The half-cell is disassembled, the negative electrode is taken out, and after being thoroughly cleaned with dimethyl carbonate, it is dried under reduced pressure at room temperature. The operation from disassembly of the non-aqueous electrolyte storage element to preparation of the negative electrode to be measured is carried out in a dry air atmosphere with a dew point of less than -40°C. Here, "normal use" refers to the use of the non-aqueous electrolyte storage element under the charge and discharge conditions recommended or specified for the non-aqueous electrolyte storage element.
[0021] (2) Acquisition of SEM images
[0022] In obtaining the SEM image, a JSM-7001F (manufactured by JEOL Ltd.) was used as a scanning electron microscope. The SEM image was used to observe the secondary electron image. The acceleration voltage was set to 15 kV. The observation magnification was set to a magnification at which the number of graphite particles appearing in one field of view was more than 3 and less than 15. The obtained SEM image was saved as an image file. In addition, the conditions such as the spot diameter, working distance, irradiation current, brightness, and focus were appropriately set in a manner that made the outline of the graphite particles clear.
[0023] (3) Cutting out the outline of graphite particles
[0024] The image cropping function of the image editing software Adobe Photoshop Elements 11 was used to crop the outline of the graphite particles from the obtained SEM image. The outline was cropped by using the quick selection tool to select the outermost edge of the outline of the graphite particles and editing the part other than the graphite particles to a black background. At this time, if the number of graphite particles with the cropped outline is less than 3, the SEM image was obtained again and cropped until the number of graphite particles with the cropped outline is more than 3.
[0025] (4) Binarization
[0026] The image of the first graphite particle among the cut graphite particles was binarized using the image analysis software PopImaging 6.00, with the concentration 20% less than the concentration with the maximum intensity set as the threshold. Based on the binarization, the area on the side with the higher concentration was calculated as the "area S1 of the voids in the particle".
[0027] Next, the image of the first graphite particle is binarized as before, using a concentration of 10% as a threshold value. The outer edge of the graphite particle is determined by the binarization process, and the area inside the outer edge is calculated as the "area S0 of the entire particle".
[0028] By using the calculated S1 and S0, the ratio of S1 to S0 (S1 / S0) is calculated to calculate the "area ratio R1 of the voids in the particle to the entire area of the particle" of the first graphite particle.
[0029] The images of the second and subsequent graphite particles among the cut graphite particles are also subjected to the above-mentioned binarization process to calculate the area S1 and the area S0. Based on the calculated area S1 and the area S0, the area ratios R2, R3, etc. of the voids of each graphite particle are calculated.
[0030] (5) Determination of the area ratio of voids
[0031] By calculating the average of the area ratios R1, R2, R3, etc. of all voids calculated by the binarization process, the "area ratio of voids in the particle to the entire area of the particle (void ratio)" is determined.
[0032] It should be noted that instead of the scanning electron microscope used for the above-mentioned "obtaining the SEM image", the image editing software used for the "cutting out the outline of the graphite particles", and the image analysis software used for the "binarization processing", it is also possible to use image editing and image analysis devices and software that can perform equivalent measurements as these.
[0033] “Graphite” refers to the average lattice spacing (d) of the (002) plane determined by X-ray diffraction before charge / discharge or in the discharged state. 002 ) is a carbon material having a diameter of 0.33 nm or more and less than 0.34 nm. Here, the "discharge state" of the carbon material refers to a discharge state in which lithium ions that can be embedded and deintercalated with charge and discharge are fully deintercalated from the carbon material as the negative electrode active material. For example, in a half-cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metal Li as a counter electrode, the open circuit voltage is 0.6 V or more.
[0034] [2]: In the non-aqueous electrolyte storage element described in [1] above, the negative electrode has a negative electrode active material layer containing the solid graphite, and the porosity of the negative electrode active material layer can be 40% or more. The negative electrode active material layer with a porosity of less than 40% is usually formed by compaction based on pressing or the like. When the pressing pressure is strong, the particles of the solid graphite are broken, and the surface area of the solid graphite increases. Therefore, after storage in a high temperature environment, tungsten elements are further precipitated on the surface of the solid graphite, the resistance is further increased, and the input energy is easily reduced. In contrast, the solid graphite particles in the negative electrode active material layer with a porosity of more than 40% are less broken, and according to the non-aqueous electrolyte storage element described in [2] above, the input energy after storage in a high temperature environment tends to be further increased.
[0035] The "porosity (%)" of the negative electrode active material layer is obtained by the calculation formula (1-V2 / V1) × 100, assuming that the apparent volume (volume including voids) of the negative electrode active material layer is V1 and the sum of the solid phase volumes of the materials constituting the negative electrode active material layer is V2. The sum V2 of the solid phase volumes of the materials constituting the negative electrode active material layer can be calculated from the content of the materials in the negative electrode active material layer and the true density of the materials.
[0036] [3]: In the non-aqueous electrolyte storage element described in [1] or [2] above, the positive electrode active material further contains a transition metal element other than the tungsten element, and the content of the tungsten element can be 0.2 mol% or more relative to the transition metal element other than the tungsten element in the positive electrode active material. According to the non-aqueous electrolyte storage element described in [3] above, the positive electrode active material contains a sufficient amount of tungsten element, so the input energy of the non-aqueous electrolyte storage element at the beginning and after storage in a high temperature environment is further increased.
[0037] [4]: In the non-aqueous electrolyte storage element described in any one of [1] to [3] above, the solid graphite may be solid natural graphite. Natural graphite has higher crystallinity than artificial graphite. Therefore, when the solid graphite is solid natural graphite, the discharge capacity per unit mass of the negative electrode active material increases, and according to the non-aqueous electrolyte storage element described in [4] above, the input energy after initial storage and storage in a high temperature environment also increases further.
[0038] [5]: In the non-aqueous electrolyte storage element described in any one of [1] to [4] above, the average particle size of the solid graphite may be 5 μm or more. When solid graphite with a large particle size is used, the surface area of the solid graphite becomes smaller, and as a result, it becomes difficult for tungsten elements to precipitate on the surface of the solid graphite. According to the non-aqueous electrolyte storage element described in [5] above, the input energy after storage in a high temperature environment is further increased.
[0039] The “average particle size” refers to a value at which the volume-based integrated distribution calculated in accordance with JIS-Z-8819-2 (2001) becomes 50% based on a particle size distribution obtained by measuring a diluted solution obtained by diluting particles with a solvent using a laser diffraction / scattering method in accordance with JIS-Z-8825 (2013).
[0040] A nonaqueous electrolyte storage element, a storage device, a method for manufacturing a nonaqueous electrolyte storage element, and other embodiments of the present invention are described in detail. It should be noted that the names of the components (components) used in each embodiment are sometimes different from the names of the components (components) used in the background art.
[0041] <Non-aqueous electrolyte energy storage device>
[0042] A nonaqueous electrolyte storage element (hereinafter, also referred to as "storage element") according to one embodiment of the present invention comprises: an electrode body having a positive electrode, a negative electrode and a separator, a nonaqueous electrolyte and a container for accommodating the electrode body and the nonaqueous electrolyte. The electrode body is usually a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked via a separator, or a wound type in which a positive electrode and a negative electrode are wound in a state of being stacked via a separator. The nonaqueous electrolyte exists in a state of being immersed in the positive electrode, the negative electrode and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also referred to as "secondary battery") is described.
[0043] (positive electrode)
[0044] The positive electrode includes a positive electrode substrate and a positive electrode active material layer provided on the positive electrode substrate directly or via an intermediate layer.
[0045] The positive electrode substrate has electrical conductivity. Whether it has electrical conductivity is determined by converting the volume resistivity measured in accordance with JIS-H-0505 (1975) into 10 7 Ω·cm is used as a threshold value for determination. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or their alloys can be used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. As the positive electrode substrate, foil, vapor-deposited film, mesh, porous material, etc. can be cited. From the viewpoint of cost, foil is preferred. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. As aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H-4160 (2006) can be exemplified.
[0046] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By making the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased and the energy density per unit volume of the secondary battery can be increased.
[0047] The intermediate layer is a layer provided between the positive electrode substrate and the positive electrode active material layer. The intermediate layer reduces the contact resistance between the positive electrode substrate and the positive electrode active material layer by containing a conductive agent such as carbon particles. The composition of the intermediate layer is not particularly limited, and for example, it contains a binder and a conductive agent.
[0048] The positive electrode active material layer contains a positive electrode active material and may contain any components such as a conductive agent, a binder (adhesive), a thickener, and a filler as necessary.
[0049] The positive electrode active material contains tungsten. The tungsten element can exist in the form of a compound such as an oxide (WO3). The compound containing tungsten, for example, covers at least a portion of the surface of particles of a substance capable of embedding and deintercalating charge transport ions such as lithium ions. In other words, the positive electrode active material can contain a substance capable of embedding and deintercalating charge transport ions and a compound containing tungsten. The positive electrode active material can also be essentially a substance consisting only of a substance capable of embedding and deintercalating charge transport ions and a compound containing tungsten. The substance capable of embedding and deintercalating charge transport ions itself can contain tungsten. The tungsten element can, for example, be present on the surface of particles of the positive electrode active material. The tungsten element can also be present inside the particles of the positive electrode active material. In this way, by making the positive electrode active material contain tungsten, the side reaction at the positive electrode can be suppressed and the conductivity of charge transport ions such as lithium ions can be improved, and the input energy of the non-aqueous electrolyte storage element can be increased. As a way to make the positive electrode active material contain tungsten, there is a way to coat the compound containing tungsten on the surface of particles of a substance capable of embedding and deintercalating charge transport ions. In addition, there is also a method of adding tungsten element during the synthesis of a material capable of embedding and de-embedding charge transport ions and sintering, so that a compound containing tungsten element is supported on the particle surface or inside of the positive electrode active material. As the positive electrode active material containing tungsten element, a commercially available product can be used.
[0050] As a substance capable of embedding and de-embedding charge transport ions, it is preferred to be a substance capable of embedding and de-embedding lithium ions, and these can use previously known materials. Examples of such substances include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, oxygen group element compounds, sulfur, and the like. Examples of lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Co (1-x-γ )]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O2(0≤x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2 (0≤x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β) etc. As lithium transition metal composite oxides having a spinel crystal structure, Li x Mn2O4、Li x Ni γ Mn (2-γ) O4, etc. As polyanion compounds, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. can be cited. As oxide compounds, titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. can be cited. Atoms or part of polyanions in these materials can be replaced by atoms or anionic species composed of other elements. One of these materials can be used alone, or two or more can be mixed and used.
[0051] As a material capable of inserting and removing charge transport ions, lithium transition metal composite oxides are preferred, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure are more preferred, and Li[Lix Ni γ Mn β Co (1-x-γ-β) ]O2 (0≤x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β). In the above Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2, for example, preferably 0.1≤γ<0.9, 0.1≤β<0.9. When such a substance is used, the effect of improving the input energy by the tungsten element is particularly effective.
[0052] The positive electrode active material preferably also contains transition metal elements other than tungsten. As a material capable of embedding and de-embedding charge transport ions, when using lithium transition metal composite oxides, polyanionic compounds, etc., the positive electrode active material also contains transition metal elements other than tungsten. The content of tungsten is preferably 0.2 mol% to 3 mol% relative to all transition metal elements other than tungsten in the positive electrode active material, and more preferably 0.5 mol% to 2 mol%. By making the content of tungsten above the lower limit, the effect of tungsten based on the positive electrode active material is fully effective, and the input energy after initial and high temperature storage is further increased. On the other hand, by making the content of tungsten below the upper limit, the ion conductivity of the positive electrode active material is improved, and the input energy after initial and high temperature storage is further increased.
[0053] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% to 99% by mass, more preferably 70% to 98% by mass, and further preferably 80% to 95% by mass. By making the content of the positive electrode active material within the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0054] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm to 20 μm. By making the average particle size of the positive electrode active material above the above lower limit, the manufacture or handling of the positive electrode active material becomes easy. By making the average particle size of the positive electrode active material below the above upper limit, the electronic conductivity of the positive electrode active material layer is improved. It should be noted that when a composite of the positive electrode active material and other materials is used, the average particle size of the composite is used as the average particle size of the positive electrode active material.
[0055] In order to obtain a powder of a predetermined particle size, a pulverizer and a classifier are used. As a pulverization method, for example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a planetary ball mill, a jet mill, a reverse jet mill, a rotating airflow jet mill or a sieve can be mentioned. During pulverization, wet pulverization in which an organic solvent such as water or hexane coexists can also be used. As a classification method, a sieve and a wind classifier can be used in a dry method and a wet method as needed.
[0056] As for the conductive agent, there is no particular limitation as long as it is a material with conductivity. As such a conductive agent, for example, carbonaceous materials, metals, conductive ceramics, etc. can be cited. As carbonaceous materials, graphite, non-graphite carbon, graphene-based carbon, etc. can be cited. As non-graphite carbon, carbon nanofibers, pitch-based carbon fibers, carbon black, etc. can be cited. As carbon black, furnace black, acetylene black, Ketjen black, etc. can be cited. As graphene-based carbon, graphene, carbon nanotubes (CNT), fullerene, etc. can be cited. As the shape of the conductive agent, powder, fiber, etc. can be cited. As the conductive agent, one of these materials can be used alone, or two or more can be mixed and used. In addition, these materials can also be used in a composite. For example, a material obtained by composite carbon black and CNT can be used. Among these, from the viewpoint of electronic conductivity and coating processability, carbon black is preferred, and acetylene black is preferred.
[0057] The content of the conductive agent in the positive electrode active material layer is preferably 1% to 10% by mass, more preferably 3% to 9% by mass. When the content of the conductive agent is within the above range, the energy density of the secondary battery can be increased.
[0058] Examples of the binder include fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), thermoplastic resins such as polyethylene, polypropylene, polyacrylic acid, and polyimide, elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), and fluororubber, and polysaccharide polymers.
[0059] The content of the binder in the positive electrode active material layer is preferably 0.5% by mass to 10% by mass, and more preferably 1% by mass to 9% by mass. When the content of the binder is within the above range, the active material can be stably retained.
[0060] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be inactivated in advance by methylation or the like.
[0061] The content of the thickener in the positive electrode active material layer may be, for example, 0.1 to 6 mass %, or 0.5 to 3 mass %. The content of the thickener in the positive electrode active material layer may be 1 mass % or less, or the positive electrode active material layer may not contain a thickener.
[0062] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, aluminum oxide, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminum silicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.
[0063] The content of the filler in the positive electrode active material layer may be, for example, 0.1% to 8% by mass, or 0.5% to 5% by mass. The content of the filler in the positive electrode active material layer may be 3% by mass or less, or 1% by mass or less, or the positive electrode active material layer may not contain any filler.
[0064] Regarding the positive electrode active material layer, typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, etc. can be contained as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0065] The mass per unit area of the positive electrode active material layer is not particularly limited, but is, for example, 4.0 mg / cm 2 ~15mg / cm 2 The lower limit of the mass per unit area of the positive electrode active material layer is preferably 4.5 mg / cm 2 , more preferably 4.8 mg / cm 2 or 5.0mg / cm 2 In some embodiments, the mass per unit area of the positive electrode active material layer can be, for example, 5.5 mg / cm 2 Above, it can also be 5.8mg / cm 2 The upper limit of the mass per unit area of the positive electrode active material layer is preferably 12 mg / cm 2 , more preferably 10 mg / cm 2. In a non-aqueous electrolyte storage element having a positive electrode active material layer whose mass per unit area is within the above-mentioned range, the application effect of the present configuration can be more appropriately exerted. It should be noted that the "mass per unit area of the positive electrode active material layer" refers to the mass per unit area of one positive electrode active material layer. For example, in a case where the positive electrode has a positive electrode substrate and positive electrode active material layers are respectively provided on both sides of the positive electrode substrate, the "mass per unit area of the positive electrode active material layer" is the mass per unit area of the positive electrode active material layer on one side. The same is true for the "mass per unit area of the negative electrode active material layer" described later.
[0066] (negative electrode)
[0067] The negative electrode comprises a negative electrode substrate and a negative electrode active material layer provided directly on the negative electrode substrate or provided via an intermediate layer. The structure of the intermediate layer is not particularly limited, and can be selected from the structures exemplified in the above-mentioned positive electrode.
[0068] The negative electrode substrate has conductivity. As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel or their alloys, carbonaceous materials, etc. are used. Among these, copper or copper alloys are preferred. As the negative electrode substrate, foil, vapor-deposited film, net, porous material, etc. can be cited, and from the viewpoint of cost, foil is preferred. Therefore, copper foil or copper alloy foil is preferably used as the negative electrode substrate. As examples of copper foil, rolled copper foil, electrolytic copper foil, etc. can be cited.
[0069] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By making the average thickness of the negative electrode substrate within the above range, the strength of the negative electrode substrate can be increased and the energy density per unit volume of the secondary battery can be increased.
[0070] The negative electrode active material layer contains a negative electrode active material and optionally contains a conductive agent, a binder, a thickener, a filler, and other optional components.
[0071] Regarding the negative electrode active material layer, typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, Ba, transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, W, etc. can be contained as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.
[0072] The negative electrode active material contains solid graphite. By making the negative electrode active material contain solid graphite, the input energy after storage in a high temperature environment also becomes larger. In the above SEM image, the area ratio (void ratio) of the voids in the particle relative to the total area of the particle where the solid graphite cross section is observed is 2% or less, preferably 1% or less, and more preferably 0.5% or less. The lower limit of the area ratio (void ratio) can be 0%.
[0073] Solid graphite can be natural graphite or artificial graphite, but natural graphite is preferred. By making solid graphite natural graphite (solid natural graphite), the discharge capacity per unit mass of the negative electrode active material becomes larger, and the input energy at the beginning and after storage in a high temperature environment becomes further larger.
[0074] Natural graphite is a general term for graphite mined from natural resources. The shape of solid natural graphite is not particularly limited, and examples thereof include flaky graphite, blocky graphite (flaky graphite), and earthy graphite. Solid natural graphite may also be spheroidized natural graphite particles obtained by spheroidizing flaky natural graphite and the like. Regarding natural graphite, in an X-ray diffraction pattern using CuKα lines measured before charge and discharge or in a discharge state, four peaks may appear in the range of 40° to 50° at a diffraction angle 2θ. These four peaks are considered to be two peaks of a structure derived from a hexagonal system and two peaks of a structure derived from a rhombohedral system. In the case of artificial graphite, it is generally believed that only two peaks of a structure derived from a hexagonal system appear. In the X-ray diffraction pattern, the ratio of the peak intensity derived from the (012) plane to the peak intensity derived from the (100) plane ((012) / (100)) is preferably 0.3 or more, and more preferably 0.4 or more. The peak intensity ratio ((012) / (100)) is preferably 0.6 or less. Here, the (100) plane is a structure derived from a hexagonal crystal system, and the (012) plane is a structure derived from a rhombohedral crystal system.
[0075] The average particle size of solid graphite can be, for example, 1 μm to 25 μm, preferably 3 μm to 20 μm, more preferably 5 μm to 15 μm, and further preferably 7 μm to 13 μm. In several embodiments, the average particle size of solid graphite can be 8 μm to 12 μm, or can be 9 μm or more. By making the average particle size of solid graphite within the above range, the charge and discharge performance of the non-aqueous electrolyte storage element can be improved. In particular, when the average particle size of solid graphite is above the above lower limit, the input energy after storage in a high temperature environment becomes larger. In order to obtain a specified particle size of solid graphite, a pulverizer, a classifier, etc. can be used. The pulverization method and the classification method can be selected, for example, from the methods exemplified in the above-mentioned positive electrode.
[0076] The content of solid graphite in the negative electrode active material layer is preferably 60% to 99.5% by mass, and more preferably 90% to 99% by mass. By making the content of solid graphite within the above range, it is possible to achieve both high energy density and manufacturability of the negative electrode active material layer, and to further increase the input after storage in a high temperature environment.
[0077] The negative electrode active material may contain other negative electrode active materials other than solid graphite. As other negative electrode active materials, hollow graphite (graphite other than solid graphite) and other various negative electrode active materials known in the past can be used. However, solid graphite is preferably the main active material. For example, in the cross-sectional SEM image of the negative electrode, the area ratio of the area occupied by solid graphite to the area occupied by the negative electrode active material (area occupied by solid graphite / area occupied by negative electrode active material) is preferably 90% or more, more preferably 99% or more, and can actually be 100%. It should be noted that the cross-sectional SEM image of the above-mentioned negative electrode is obtained by the same steps as the SEM image when determining the "area ratio (void ratio) of the intra-particle voids to the area of the entire particle" of the graphite particles. Make the area occupied by the negative electrode active material the area of the entire particle of the negative electrode active material (including the area of the voids). It should be noted that the cross-sectional SEM image of particles containing more than 10 negative electrode active materials in one field of view is used to obtain the area ratio of the area occupied by solid graphite relative to the area occupied by the negative electrode active material (area occupied by solid graphite / area occupied by negative electrode active material). In addition, the content of solid graphite occupied by all negative electrode active materials contained in the negative electrode active material layer is preferably 90% by mass or more, more preferably 99% by mass or more, and in fact can also be 100% by mass. That is, it is particularly preferred to use only solid graphite as a negative electrode active material. In this way, by mainly using solid graphite as the negative electrode active material, the input energy after storage in a high temperature environment is further increased.
[0078] The total negative electrode active material content of the negative electrode active material layer is preferably 60% to 99.5% by mass, more preferably 90% to 99% by mass. By setting the total negative electrode active material content within the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.
[0079] The conductive agent, binder, thickener, filler, etc., which are optional components of the negative electrode active material layer, can be selected from the materials exemplified in the positive electrode. However, the graphite containing the negative electrode active material layer does not contain a conductive agent.
[0080] The content of the conductive agent in the negative electrode active material layer may be 3% by mass or less or 1% by mass or less, and the negative electrode active material layer may not contain the conductive agent.
[0081] The content of the binder in the negative electrode active material layer is preferably 0.5% by mass to 5% by mass, and more preferably 0.8% by mass to 3% by mass.
[0082] The content of the thickener in the negative electrode active material layer is, for example, preferably 0.1% by mass to 6% by mass, and more preferably 0.5% by mass to 3% by mass.
[0083] The content of the filler in the negative electrode active material layer may be, for example, 0.1% to 8% by mass, or 0.5% to 5% by mass. The content of the filler in the negative electrode active material layer may be 3% by mass or less, or 1% by mass or less, and the negative electrode active material layer may not contain any filler.
[0084] The porosity of the negative electrode active material layer can be set to 30% to 60%, for example. As the lower limit of the porosity, it is preferably 35%, more preferably 38%, further preferably 40%, and most preferably 42%. By making the porosity of the negative electrode active material layer above the above lower limit, the input energy of the non-aqueous electrolyte storage element, especially the input energy after storage in a high temperature environment, can be further increased. On the other hand, as the upper limit of the above porosity, it is preferably 55%, more preferably 50%, and further preferably 48%. The porosity of the negative electrode active material layer can be adjusted by the particle size of solid graphite, the presence or absence of pressing during manufacturing, the pressing pressure, etc.
[0085] The mass per unit area of the negative electrode active material layer is not particularly limited, but is, for example, 2.0 mg / cm 2 ~12mg / cm 2 The lower limit of the mass per unit area of the negative electrode active material layer is preferably 2.2 mg / cm 2 , more preferably 2.5 mg / cm 2 or 2.8 mg / cm 2 In some embodiments, the mass per unit area of the negative electrode active material layer can be, for example, 3.0 mg / cm 2 Above, 3.5 mg / cm 2 The upper limit of the mass per unit area of the negative electrode active material layer is preferably 10 mg / cm 2 , more preferably 8.0 mg / cm 2 or 6.0mg / cm 2 In a non-aqueous electrolyte storage device including a negative electrode active material layer having a mass per unit area within the above range, the application effect of the present configuration can be more appropriately exerted.
[0086] Although not particularly limited, the lower limit of the ratio of the mass of solid graphite per unit area contained in the negative electrode active material layer to the mass of tungsten element per unit area contained in the positive electrode active material layer can be approximately about 25. As the lower limit of the ratio, it is preferably 30, and sometimes more preferably 32, 34 or 36. On the other hand, as the upper limit of the ratio, it is preferably 100, and sometimes more preferably 80, 70, 60 or 45. In a non-aqueous electrolyte storage element in which the ratio is within the above range, the application effect of the present structure can be further appropriately exerted. The ratio of the mass of solid graphite per unit area contained in the negative electrode active material layer to the mass of tungsten element per unit area contained in the positive electrode active material layer can be adjusted according to the content of tungsten element in the positive electrode active material, the content of solid graphite in the negative electrode active material, the mass per unit area (coating mass) of the positive electrode active material layer and the negative electrode active material layer, etc.
[0087] (Isolator)
[0088] The separator can be appropriately selected from known separators. As the separator, for example, a separator consisting only of a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and an adhesive is formed on one side or both sides of the substrate layer, etc. can be used. As the shape of the substrate layer of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be cited. Among these shapes, from the viewpoint of strength, porous resin films are preferred, and from the viewpoint of liquid retention of non-aqueous electrolytes, non-woven fabrics are preferred. As the material of the substrate layer of the separator, from the viewpoint of the cutting function, for example, polyolefins such as polyethylene and polypropylene are preferred, and from the viewpoint of anti-oxidative decomposition, for example, polyimides and aromatic polyamides are preferred. As the substrate layer of the separator, a material composited with these resins can be used.
[0089] The heat-resistant particles contained in the heat-resistant layer are preferably heat-resistant particles whose mass reduction is 5% or less when the temperature is increased from room temperature to 500°C in an air atmosphere of 1 atmosphere, and more preferably heat-resistant particles whose mass reduction is 5% or less when the temperature is increased from room temperature to 800°C. Inorganic compounds can be cited as materials whose mass reduction is below the prescribed value. As inorganic compounds, for example, oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, aluminum silicate, nitrides such as aluminum nitride and silicon nitride, carbonates such as calcium carbonate, sulfates such as barium sulfate, insoluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate, shared bonding crystals such as silicon and diamond, talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, mica, etc., derived from mineral resources or their artificial products, etc. As the inorganic compound, a single substance or a composite of these substances may be used alone, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide or aluminum silicate is preferred from the viewpoint of safety of the storage element.
[0090] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and preferably 20% by volume or more from the viewpoint of discharge performance. Here, the "porosity" is a value based on volume, and means a value measured using a mercury porosimeter.
[0091] As a separator, a polymer gel composed of a polymer and a non-aqueous electrolyte can be used. As polymers, for example, polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyvinylidene fluoride, etc. can be cited. If a polymer gel is used, it has the effect of suppressing leakage. As a separator, a porous resin film or nonwoven fabric as described above can be used together with a polymer gel.
[0092] (Non-aqueous electrolyte)
[0093] The non-aqueous electrolyte can be appropriately selected from known non-aqueous electrolytes. The non-aqueous electrolyte can be a non-aqueous electrolyte solution. The non-aqueous electrolyte solution contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.
[0094] As nonaqueous solvent, can be suitably selected from known nonaqueous solvents.As nonaqueous solvent, can enumerate cyclic carbonate, linear carbonate, carboxylate, phosphoric acid ester, sulfonic acid ester, ether, amides, nitrile etc.As nonaqueous solvent, also can use the compound that the part of the hydrogen atom that their compound comprises is replaced by halogen.
[0095] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.
[0096] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, ethyl trifluoromethyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferred.
[0097] As the non-aqueous solvent, it is preferred to use a cyclic carbonate or a chain carbonate, and it is more preferred to use a cyclic carbonate and a chain carbonate in combination. By using a cyclic carbonate, the dissociation of the electrolyte salt can be promoted to improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, the viscosity of the non-aqueous electrolyte can be kept reduced. In the case of using a cyclic carbonate and a chain carbonate in combination, the volume ratio of the cyclic carbonate and the chain carbonate (cyclic carbonate: chain carbonate) is preferably in the range of 5:95 to 50:50, for example.
[0098] The electrolyte salt may be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts. Among these, lithium salts are preferred.
[0099] As lithium salts, inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate) borate (LiBOB), lithium difluorooxalate borate (LiFOB), lithium oxalate salts such as lithium bis(oxalate) difluorophosphate (LiFOP), lithium salts having halogenated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3 can be cited. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0100] When the non-aqueous electrolyte contains LiPF6, LiPF6 easily reacts with a small amount of water in the non-aqueous electrolyte to generate HF. The presence of HF in the non-aqueous electrolyte promotes the dissolution of tungsten from the positive electrode active material into the non-aqueous electrolyte. In addition, when there is an electrolyte salt having anions containing fluorine elements, oxygen elements, and phosphorus elements such as LiPO2F2 and lithium bis(oxalate) difluorophosphate (LiFOP) in the non-aqueous electrolyte, the dissolution of tungsten from the positive electrode active material into the non-aqueous electrolyte is further promoted. Therefore, in the case where a non-aqueous electrolyte storage element using a non-aqueous electrolyte containing such a component is an embodiment of the present invention, the effect of increasing the input energy after storage in a high temperature environment is particularly significant. The content of the electrolyte salt having anions containing fluorine elements, oxygen elements, and phosphorus elements in the non-aqueous electrolyte can be, for example, 0.01 mol / dm at 20°C and 1 atmosphere. 3 ~0.5mol / dm 3 , or 0.03 mol / dm 3 ~0.3mol / dm 3 , can also be 0.05mol / dm 3 ~0.2mol / dm 3 .
[0101] The content of the electrolyte salt in the non-aqueous electrolyte is preferably 0.1 mol / dm 3 ~2.5mol / dm 3 , more preferably 0.3 mol / dm 3 ~2.0mol / dm 3 , more preferably 0.5 mol / dm 3 ~1.7mol / dm 3 , particularly preferably 0.7 mol / dm 3 ~1.5mol / dm 3 By setting the content of the electrolyte salt to be within the above range, the ion conductivity of the non-aqueous electrolyte can be improved.
[0102] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, triphenyl, partially hydrogenated triphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and diphenylfuran, partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene, halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole, vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutamic anhydride, itaconic anhydride, cyclohexane dicarbonic anhydride, ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate Ester, butyl dimethanesulfonate (Busulfan), methyl toluenesulfonate, dimethyl sulfate, vinyl sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxa-1,3,2-dioxatetrahydrothiophene), 4-methylsulfonyloxymethyl-2,2-dioxa-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, bispyridine disulfide, 1,3-propylene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsiloxy titanate, etc. These additives may be used alone or in combination of two or more.
[0103] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% to 10% by mass relative to the mass of the entire non-aqueous electrolyte, more preferably 0.1% to 7% by mass, further preferably 0.2% to 5% by mass, and particularly preferably 0.3% to 3% by mass. By making the content of the additive within the above range, the capacity retention performance or cycle performance after high temperature storage can be improved, and the safety can be further improved.
[0104] As the non-aqueous electrolyte, a solid electrolyte may be used, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0105] The solid electrolyte has ion conductivity of lithium, sodium, calcium, etc., and can be selected from any material that is solid at room temperature (e.g., 15° C. to 25° C.). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, polymer solid electrolytes, and the like.
[0106] In the case of lithium ion secondary batteries, examples of sulfide solid electrolytes include Li2S-P2S5, LiI-Li2S-P2S5, Li 10Ge-P2S 12 wait.
[0107] The shape of the nonaqueous electrolyte storage element of the present embodiment is not particularly limited, and examples thereof include cylindrical batteries, square batteries, flat batteries, coin batteries, button batteries, and the like.
[0108] Figure 1 A non-aqueous electrolyte storage element 1 is shown as an example of a square battery. It should be noted that this figure is a perspective view of the inside of a container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator is housed in a square container 3. The positive electrode is electrically connected to a positive terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative terminal 5 via a negative electrode lead 51.
[0109] <Electricity storage device>
[0110] The non-aqueous electrolyte storage element of the present embodiment is a storage unit (battery module) composed of a plurality of non-aqueous electrolyte storage elements, and can be mounted on a power supply for vehicles such as electric vehicles (EV), hybrid vehicles (HEV), plug-in hybrid electric vehicles (PHEV), a power supply for electronic devices such as personal computers and communication terminals, or a power supply for power storage, etc. In this case, the technology of the present invention can be applied to at least one non-aqueous electrolyte storage element contained in the storage unit.
[0111] Figure 2 An example of an electricity storage device 30 is shown in which an electricity storage unit 20 formed by collecting two or more electrically connected non-aqueous electrolyte storage elements 1 is further collected. The electricity storage device 30 may include a bus bar (not shown) that electrically connects the two or more non-aqueous electrolyte storage elements 1, a bus bar (not shown) that electrically connects the two or more electricity storage units 20, etc. The electricity storage unit 20 or the electricity storage device 30 may include a state monitoring device (not shown) that monitors the state of one or more non-aqueous electrolyte storage elements.
[0112] <Method for producing non-aqueous electrolyte storage element>
[0113] The manufacturing method of the non-aqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method, for example, comprises: a step of preparing an electrode body, a step of preparing a non-aqueous electrolyte, and a step of storing the electrode body and the non-aqueous electrolyte in a container. The step of preparing the electrode body comprises: a step of preparing a positive electrode and a negative electrode, and a step of forming an electrode body by stacking or winding the positive electrode and the negative electrode through a separator.
[0114] The process of preparing the positive electrode can be performed, for example, by applying a positive electrode mixture paste directly or via an intermediate layer on the positive electrode substrate and drying it. The positive electrode mixture paste contains a positive electrode active material, components constituting a positive electrode active material layer, and a dispersion medium. After the applied positive electrode mixture paste is dried, it can be pressed, etc.
[0115] The process of preparing the negative electrode can be performed, for example, by applying a negative electrode mixture paste directly or via an intermediate layer on the negative electrode substrate and drying it. The negative electrode mixture slurry contains solid graphite, etc., various components constituting the negative electrode active material layer, and a dispersion medium. After the applied negative electrode mixture paste is dried, pressing can be used. The porosity of the formed negative electrode active material layer can be adjusted by the presence or absence of the pressing and the pressing pressure.
[0116] The step of storing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution can be injected from an injection port formed in the container and then the injection port can be sealed.
[0117] <Other embodiments>
[0118] It should be noted that the nonaqueous electrolyte storage element of the present invention is not limited to the above-mentioned embodiment, and various changes can be added within the scope of the gist of the present invention. For example, the structure of other embodiments can be added to the structure of a certain embodiment, and a part of the structure of a certain embodiment can be replaced with the structure of other embodiments or known technology. And a part of the structure of a certain embodiment can be deleted. In addition, known technology can be added to the structure of a certain embodiment.
[0119] In the above embodiment, the case of using a non-aqueous electrolyte storage element as a non-aqueous electrolyte secondary battery (lithium ion secondary battery) capable of charge and discharge is described, and the type, shape, size, capacity, etc. of the non-aqueous electrolyte storage element are arbitrary. The present invention can also be applied to capacitors such as various secondary batteries, double-layer capacitors or lithium ion capacitors.
[0120] In the above embodiment, the positive electrode and the negative electrode are stacked with a separator, but the electrode body may not have a separator. For example, the positive electrode and the negative electrode may be directly connected with a non-conductive layer formed on the active material layer of the positive electrode or the negative electrode.
[0121] Example
[0122] Hereinafter, the present invention will be described in more detail based on examples, but the present invention is not limited to the following examples.
[0123] [Example 1]
[0124] (Production of positive electrode)
[0125] Preparation for attaching tungsten oxide to LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The positive electrode active material on the surface of the particle of O2 has a tungsten content of 1 mol % relative to the transition metal element other than tungsten in the positive electrode active material.
[0126] The positive electrode mixture paste is prepared using the above-mentioned positive electrode active material, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersant. It should be noted that the mass ratio of the positive electrode active material, AB, and PVDF is 93:5:2 (converted to solid content). The coating mass (mass of solid content) of the positive electrode mixture paste is made to be 6 mg / cm on both sides of the aluminum foil serving as the positive electrode substrate. 2 The coating is performed and dried, and then roll pressing is performed to obtain a positive electrode having positive electrode active material layers stacked on both sides of the positive electrode substrate.
[0127] (Preparation of negative electrode)
[0128] The negative electrode mixture paste is prepared using solid graphite (solid natural graphite, porosity of 0.45%, average particle size of 9.9 μm) as the negative electrode active material, styrene-butadiene rubber (SBR) as the binder, carboxymethyl cellulose (CMC) as the thickener, and water as the dispersion medium. It should be noted that the mass ratio of solid graphite, SBR and CMC is set to 98.5:1:0.5 (solid content conversion). The coating mass (solid content mass) of the negative electrode mixture paste is made 4 mg / cm on both sides of the copper foil as the negative electrode substrate. 2 The coating was performed and dried. Then, roll pressing was performed to obtain a negative electrode having negative electrode active material layers stacked on both sides of the negative electrode substrate. The porosity of the negative electrode active material layer was 45%.
[0129] (Non-aqueous electrolyte)
[0130] LiPF6 was added at a concentration of 1.2 mol / dm in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 30:70. 3 The concentration of LiPO2F2 is dissolved at a concentration of 1 mass % to obtain a non-aqueous electrolyte.
[0131] (Isolator)
[0132] A polyolefin microporous film was used as the separator.
[0133] (Assembly of non-aqueous electrolyte storage element)
[0134] The positive electrode, negative electrode and separator were used to obtain a wound electrode assembly. The electrode assembly was placed in a container, a nonaqueous electrolyte solution was injected and the container was sealed to obtain a nonaqueous electrolyte storage device of Example 1.
[0135] [Examples 2 to 4, Comparative Examples 1 to 3]
[0136] The nonaqueous electrolyte storage devices of Examples 2 to 4 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1 except that the types of the positive and negative electrode active materials and the porosity of the negative electrode active material layer were as shown in Tables 1 and 2.
[0137] In the column of "Presence or absence of positive electrode active material W (tungsten element)" in Tables 1 and 2, "Presence" indicates that the positive electrode active material used in Example 1, and "Absence" indicates that the positive electrode active material does not contain tungsten element, indicating that LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2. "Hollow graphite" means hollow natural graphite with a porosity of 3% and an average particle size of 9.1 μm. The porosity of the negative electrode active material layer is adjusted by changing the pressure during pressing. In addition, Example 1 is described in both Table 1 and Table 2.
[0138] [evaluate]
[0139] (1-1) Initial charge and discharge
[0140] Each non-aqueous electrolyte storage element obtained was initially charged and discharged under the following conditions. In a thermostatic chamber at 25°C, constant current charging was performed with a charging current of 1.0C and a charge end voltage of 4.10V, and then constant voltage charging was performed at 4.10V. The charging was terminated with a total charging time of 3 hours. Then, a rest period of 10 minutes was set. Constant current discharge was performed with a discharge current of 1.0C and a discharge end voltage of 3.0V.
[0141] (1-2) Determination of initial input energy
[0142] For each non-aqueous electrolyte storage element after the initial charge and discharge, constant current charging is performed at a charging current of 1.0C in a constant temperature chamber at 25°C, and the SOC is adjusted to 50%. After being stored in a constant temperature chamber at -30°C for 4 hours, constant current charging is performed for 10 seconds at 5C, 10C, 15C, 20C or 25C. After each charge is completed, constant current discharge is performed at a current of 1.0C, and the SOC is set to 50%. The resistance value is calculated from the slope of the current of each charge and the voltage 1 second after the start of charging, and "{the difference between the voltage before charging and the upper limit voltage (4.3V)} / resistance value×upper limit voltage (4.3V)" is calculated as the initial input energy. It should be noted that input energy refers to the energy (power) that can be obtained per unit time.
[0143] (1-3) Measurement of input energy after storage in a high temperature environment
[0144] Next, each nonaqueous electrolyte storage element was charged at a constant current and constant voltage at a charging current of 1.0C in a thermostatic chamber at 25°C, and the SOC was set to 80%. Each nonaqueous electrolyte storage element was stored in a thermostatic chamber at 80°C for 10 days at the SOC of 80%. Then, after being stored in a thermostatic chamber at 25°C for more than 3 hours, constant current discharge was performed at a discharge current of 1.0C and a discharge end voltage of 3.0V, and the input energy was calculated in the same manner as the initial input energy, as the input energy after storage (the input energy after storage in a high temperature environment).
[0145] Tables 1 and 2 show the initial energy input and the energy input after storage of each nonaqueous electrolyte storage element.
[0146] [Table 1]
[0147]
[0148] [Table 2]
[0149]
[0150] As shown in Table 1, the initial input energy of each nonaqueous electrolyte storage element of Comparative Examples 2 and 3 in which the positive electrode active material does not contain tungsten is small. Although the initial input energy of the nonaqueous electrolyte storage element of Comparative Example 1 in which the positive electrode active material contains tungsten and the negative electrode active material is hollow graphite is large, the input energy after storage is small. In contrast, the nonaqueous electrolyte storage element of Example 1 in which the positive electrode active material contains tungsten and the negative electrode active material is solid graphite results in a large initial input energy and a large input energy after storage. In addition, as shown in Table 2, it was found that by increasing the porosity of the negative electrode active material layer, there is a tendency for the input energy, especially the input energy after storage, to increase.
[0151] Possibility of industrial application
[0152] The present invention can be applied to non-aqueous electrolyte storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.
[0153] Explanation of symbols
[0154] 1 Non-aqueous electrolyte storage element
[0155] 2 Electrode body
[0156] 3 Container
[0157] 4 Positive terminal
[0158] 41 Positive wire
[0159] 5 Negative terminal
[0160] 51 Negative lead
[0161] 20 Storage unit
[0162] 30 Power storage device
Claims
1. A non-aqueous electrolyte storage element comprising: A positive electrode comprising a positive electrode active material containing a tungsten element, and The negative electrode contains solid graphite.
2. The nonaqueous electrolyte storage element according to claim 1, wherein The negative electrode has a negative electrode active material layer containing the solid graphite. The porosity of the negative electrode active material layer is greater than 40%.
3. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein: The positive electrode active material further contains a transition metal element other than the tungsten element. The content of the tungsten element is 0.2 mol % or more relative to the transition metal element other than the tungsten element in the positive electrode active material.
4. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein The solid graphite is solid natural graphite.
5. The nonaqueous electrolyte storage element according to claim 1 or 2, wherein: The average particle size of the solid graphite is greater than 5 μm.
Citation Information
Patent Citations
Positive electrode material for lithium secondary battery, positive electrode and lithium secondary battery
JP2001006676A
Negative pole material for lithium battery, and lithium battery
JP2005222933A